Skin Recurrence of Transformed Mycosis Fungoides Postumbilical Cord Blood Transplant despite Complete Donor Chimerism. (11th December 2014) - Pawar, Rahul; Kasi Loknath Kumar, Anup; Woodroof, Janet; Cui, Wei; McGuirk, Joseph; Abhyankar, Sunil; Ganguly, Sid; Singh, Anurag; Lin, Tara; Aljitawi, Omar
Abstract : Background. Allogeneic stem cell transplant is the treatment of choice for systemic cutaneous T-cell lymphoma (CTCL) which provides graft-versus-lymphoma effect. Herein we discuss a case of recurrence of CTCL skin lesions after cord blood transplant in a patient who continued to have 100% donor chimerism in bone marrow. Case Presentation. A 48-year-old female with history of mycosis fungoides (MF) presented with biopsy proven large cell transformation of MF. PET scan revealed multiple adenopathy in abdomen and chest suspicious for lymphoma and skin biopsy showed large cell transformation. She was treated with multiple cycles of chemotherapy. Posttherapy PET scan showed resolution of lymphadenopathy. Later she underwent ablative preparative regimen followed by single cord blood transplant. Bone marrow chimerism studies at day +60 after transplant showed 100% donor cells without presence of lymphoma. However 5 months after transplant she had recurrence of MF with the same genotype as prior skin lesion. Bone marrow chimerism study continued to show 100% donor cells. Conclusion. A differential graft-versus-lymphoma effect in our case prevented lymphoma recurrence systemically but failed to do so in skin. We hypothesize that this response may be due to presence of other factors in the bone marrow and lymph node microenvironments preventing recurrence in these sites.